2016
DOI: 10.1007/978-3-319-27511-6_3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leukemia Inhibitory Factor Receptor Signaling in Skeletal Muscle Growth, Injury and Disease

Abstract: Cytokines are an incredibly diverse group of secreted proteins with equally diverse functions. The actions of cytokines are mediated by the unique and sometimes overlapping receptors to which the soluble ligands bind. Classified within the interleukin-6 family of cytokines are leukemia inhibitory factor (LIF), oncostatin-M (OSM), cardiotrophin-1 (CT-1) and ciliary neurotrophic factor (CNTF). These cytokines all bind to the leukemia inhibitory factor receptor (LIFR) and gp130, and in some cases an additional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 72 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…CNTFR-A is a cytokine receptor that is secreted from both neurons and skeletal muscle cells, but tissue-specific deletion studies revealed that these tissues play a non-redundant role in NMJ function [11,12]. CNTFR is released in a soluble functional form and attached to the extracellular surface of PMs by a glycosylphosphatidylinositol linkage where it functions as a co-receptor along with leukemia inhibitory factor receptor (LIFR) and gp130[13]. Ligands for this receptor complex include CNTF, cytokine like factor-1, and cardiotrophin-like cytokine factor 1 although studies suggest that the latter two are likely the ligands responsible for muscle terminal maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…CNTFR-A is a cytokine receptor that is secreted from both neurons and skeletal muscle cells, but tissue-specific deletion studies revealed that these tissues play a non-redundant role in NMJ function [11,12]. CNTFR is released in a soluble functional form and attached to the extracellular surface of PMs by a glycosylphosphatidylinositol linkage where it functions as a co-receptor along with leukemia inhibitory factor receptor (LIFR) and gp130[13]. Ligands for this receptor complex include CNTF, cytokine like factor-1, and cardiotrophin-like cytokine factor 1 although studies suggest that the latter two are likely the ligands responsible for muscle terminal maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle serves as both a biological target and a source of the IL-6 family of cytokines. Two members of the IL-6 family, IL-6 and leukemia inhibitory factor (LIF), play recognized roles in both skeletal muscle hypertrophy and atrophy (26,45). Plasma elevation and muscle production of IL-6 and LIF occur under physiological conditions, involving repeated contractions during exercise and overload or muscle injury (10,18).…”
mentioning
confidence: 99%
“…However, LIFR could not activate the STAT3 pathway, which suggested that LIFR did not function through the STAT3 pathway in HTR8/SVneo cells. LIFR is an important receptor of several members of interleukin 6 family, such as leukemia inhibitory factor (LIF), oncostatin M (OSM), cardiotrophin 1 (CT1) and ciliary neurotrophic factor (CNTF) (Plun-Favreau et al 2003, Hunt & White 2016. It mediates many signaling pathways in different cells and tissues, including JAK/STAT3, MAPK/ERK1/2, MAPK/p38 and PI3K/AKT (Schiemann et al 1995, Godoy-Tundidor et al 2005, Magni et al 2007.…”
Section: Discussionmentioning
confidence: 99%